LES CONTRAINTES LIEES A L’INTEGRATION DU TIC DANS L’ENSEIGNEMENT DES SCIENCES DE LA VIE ET DE LA TERRE AU MAROC - El Madhi, Youssef; Chiahou, Brahim; Belghyti, Driss; El Kharrim, Khadija; El Halouani, Hassan (European Scientific Journal, ESJ, 2014)
The deep transformations that the international education system iswitnessingmakesit a necessity for the Moroccaneducational system to integrate the techniques of communication and information in the teachingprocess.This researchaimsatpresenting the current situation of integrating the ICT in teaching the sciences of life and earth in the city of Khemisset as well as the challenges related to it. The results of the researchteach us thatthereis no real pedagogicalintegration in this regard. Thus, everyattempt of introducingtheseinnovative techniques in teaching are to takeintoaccount the obstacles underscored in ourfieldresearch.